Sequence of growth spurts in specific dimensions in adolescents grouped by sport activity status - Geithner, C. A.; Satake, T.; Woynarowska, B.; Malina, R. M. (Medicine & Science in Sports & Exercise, 1998)
Growth spurt sequences in seven body dimensions were examined in Males (N = 52) and females (N = 49) grouped by sporting activity status: regularly training for sport (M = 21; F = 23) and non-sport persons (M = 31; F = 26). All Ss participated in regular physical education lessons at school. Growth curves were developed for both groups after a period of observation that continued in Ss from 11 to 18 years of age. The age of peak growth velocity in stature, upper segment length, and weight was earlier for male athletes than male non-athletes. Peak velocities for biacromial and bicristal breadths were greater in female athletes than non-athletes. There does not appear to be any consistent effect of sport participation on growth factors. The differences reported in this study are differentiated by gender and completely unrelated across genders. There is no obvious explanation for these results. Implication. The discovery of obvious benefits of sport participation on growth is still waiting.